DETERMINASI HARGA SAHAM SYARIAH MELALUI ANALISIS TERHADAP FAKTOR FUNDAMENTAL DAN MAKRO EKONOMI - Taufiq Akbar; Adam Afiezan (Fakultas Ekonomi, Universitas Negeri Jakarta, 2018)
In the globalization era, Investment becomes something that should be prepared to face the future. Investment instruments in Indonesia were initially conventional. With its predominantly Muslim population, Indonesia must have investment instruments in accordance to sharia principles. In line with the demands of globalization, sharia investment instruments also developed including investment instruments in Indonesia such as sharia-based investment. Sharia stocks in Indonesia show growth. It can be swon bythe sharia stock market capitalization that continues to increase throughout the year. But behind it, there are many things that should be observed. Such as the fundamental factors of the company and what macroeconomic factors affect the growth rate of Sharia stocks. This study aims to analyze and obtain empirical evidence about the influence of fundamental factors and macroeconomic factors on Islamic stocks listed in the Jakarta Islamic Index. Sample is chosen by using purposive sampling method. Companies that become sample as many as 22 companies listed in JII in the second quarter period 2015 until second quarter of 2016. The regretion analysis is used and the hypothesis is tested by t-test, f-test and r-square. The results show partially only debt to equity ratio that significantly influence the stock price, while return on assets, inflation and Bank Indonesia interest rates has no effect on stock prices. Simultaneously all variables affect the stock price. The proportion of indepen variables influence on the stock price is 48.5%, while 51.5% is influenced by other variables that not examined in this research. So, the investor in JII should be concern with fundamental factor of company's share stock especially of debt to equity ratio. Keywords: Internal and external factor, Investment instrument, Sharia share.